On the Sculpturings of Cups and Concentric Rings observed on Stones and Rocks in various parts of Scotland, &c (Proceedings of the Society of Antiquaries of Scotland, 1865)
A notice that a full paper on this topic will be printed in the Proceedings at a later date.